Marketing Principles for Attracting Foreign Students to Russian Universities - Irina Y. OKOLNISHNIKOVA; Alena A. FEKLICHEVA; Viktor M. KATOCHKOV; Eriskhan M. GESHAEV (Communications of International Proceedings, 2021)
In this study, the authors consider the marketing principles that are already actively used by Russian universities, as well as the topical principles of attracting foreign students that have not yet been included in the strategy of universities. The purpose of the study is to identify imperfections in the marketing strategy for attracting foreign students by Russian universities and to consider new promising methods for attracting potential students, based on the experience of foreign universities included in the QS and ARWU ratings.
Keywords: Marketing strategies; Russian universities; foreign students; digital-marketing; targeting; SMM.